Використання P2P та клієнт-серверних моделей у багатокористувацьких іграх - Кулик, О. О. (ХНУРЕ, 2024)
This paper explores the evolving landscape of multiplayer game architecture, highlighting the transition from traditional client-server models to innovative peer-to-peer (P2P) frameworks and the emergence of hybrid systems. It delves into the technical challenges and solutions inherent in designing scalable, efficient, and secure multiplayer experiences.
Keywords: клієнт-серверна модель; багатокористувацька гра